Kepraktisan LKPD aritmatika sosial dengan berbantuan live worksheets pada siswa SMP - Khofia, Nida; Chotimah, Siti (IKIP Siliwangi, 2023)
The development that produces LKPD product with the help of web live worksheets is the goal of this research. This type of research is research and development or RnD with the development model used according to Brog and Gall. This research was conducted in one of the junior high schools located in Bandung Regency with LKPD assisted by live worksheets as the object of research and using a realistic mathematics education approach. The subjects in this study were students of class VIII-A, totaling 10 and 30 students of class VII-C of SMP Al-Tamimi. Data collection in this study is a research instrument in the form of LKPD validation sheets from two Mathematics Education lecturers and one mathematics teacher as well as student response questionnaires obtained in limited trials and broad trials. The data analysis technique in this study is an analysis of data validation and practicality using Microsoft Excel. The results of the data collected show that the average value of the validation results of LKPD assisted by live worksheets is 85.8% with a very valid category, while the student responses obtained from questionnaire data show a result of 81.4% which is in the very practical category.